EFEKTIVITAS PENGEMBALIAN PIUTANG DANA SIMPAN PINJAM KELOMPOK PEREMPUAN PADA UNIT PENGELOLA KEGIATAN PNPM KABUPATEN POHUWATO - Misrah Misrah (AkMen JURNAL ILMIAH, 2014)
This study aims determine the savings and loan management system, determine the development of savings and loan refunds on activities management unit (CGU) in District Buntulia PNPM Pohuwato. The results showed that the system of management of the national community empowerment program (PNPM) in District Buntulia Pohuwato already accomplished in accordance with existing procedures so that funds are available ranging from 2009 to 2010 have been realized or spread throughout poor communities, especially in the group of women who want pioneering venture or want to develop their business better and more developed in the District Buntulia Pohuwato district. PNPM funds are dispersed to the community, especially the women's savings and credit groups in the period 2009-2010 in six villages in kacamatan Buntulian Pohuwato of Rp . 1.449125 billion, the Village Sipatana of Rp . 218 500 000, Village Middle Buntulia of Rp. 221 500 000, North Buntulia Village of Rp.335.000.000, Taluduyunu village of Rp . 194 375 000, North Taluduyunu Desa of Rp . 172 million, Desa Indah Karya Rp. 174 750 000, and Hulawa village of Rp . 133,000,000